Targeted Alpha Therapy: All We Need to Know about 225Ac's Physical Characteristics and Production as a Potential Theranostic Radionuclide - Wael Jalloul; Vlad Ghizdovat; Cati Raluca Stolniceanu; Teodor Ionescu; Irena Cristina Grierosu; Ioana Pavaleanu; Mihaela Moscalu; Cipriana Stefanescu (MDPI AG, 2023)
The high energy of α emitters, and the strong linear energy transfer that goes along with it, lead to very efficient cell killing through DNA damage. Moreover, the degree of oxygenation and the cell cycle state have no impact on these effects. Therefore, α radioisotopes can offer a treatment choice to individuals who are not responding to β− or gamma-radiation therapy or chemotherapy drugs. Only a few α-particle emitters are suitable for targeted alpha therapy (TAT) and clinical applications. The majority of available clinical research involves 225Ac and its daughter nuclide 213Bi. Additionally, the 225Ac disintegration cascade generates γ decays that can be used in single-photon emission computed tomography (SPECT) imaging, expanding the potential theranostic applications in nuclear medicine. Despite the growing interest in applying 225Ac, the restricted global accessibility of this radioisotope makes it difficult to conduct extensive clinical trials for many radiopharmaceutical candidates. To boost the availability of 225Ac, along with its clinical and potential theranostic applications, this review attempts to highlight the fundamental physical properties of this α-particle-emitting isotope, as well as its existing and possible production methods.